BIGD Reflections 2020 - Brac Institute of Governance and Development (Brac University, 2022)
2020 was a challenging year for BIGD, one that forced us to think hard about our role in tackling the COVID-19 pandemic, by building on our core strengths and identifying areas where we could push the boundaries. As a knowledge organization, we at BIGD implemented several strategic initiatives to adapt to the rapidly evolving crisis, which helped cement our role as a policy and practice-focused, applied social science research institute. As we march ahead in 2021, we would like to take a moment to take a step back and reflect on our journey of resilience in 2020.